2014
DOI: 10.1371/journal.pone.0112545
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin-LIGHT Pathway Regulates the Interferon Signature in Rheumatoid Arthritis

Abstract: A subset of patients with autoimmune diseases including rheumatoid arthritis (RA) and lupus appear to be exposed continually to interferon (IFN) as evidenced by elevated expression of IFN induced genes in blood cells. In lupus, detection of endogenous chromatin complexes by the innate sensing machinery is the suspected driver for the IFN, but the actual mechanisms remain unknown in all of these diseases. We investigated in two randomized clinical trials the effects on RA patients of baminercept, a lymphotoxin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 75 publications
0
37
0
Order By: Relevance
“…Importantly, a recently published clinical trial in psoriatic arthritis has shown that LTbR-Ig therapy has the capacity to reduce the IFN-I signature in those arthritic patients that exhibit such a signature pretreatment, linking the LT pathway with IFN-I production in humans in vivo (53). In conclusion, inhibitors of the LT pathway, through their effect on IFN-I production, may have therapeutic potential in CD8 + T cell-driven disease states.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, a recently published clinical trial in psoriatic arthritis has shown that LTbR-Ig therapy has the capacity to reduce the IFN-I signature in those arthritic patients that exhibit such a signature pretreatment, linking the LT pathway with IFN-I production in humans in vivo (53). In conclusion, inhibitors of the LT pathway, through their effect on IFN-I production, may have therapeutic potential in CD8 + T cell-driven disease states.…”
Section: Discussionmentioning
confidence: 92%
“…This finding, together with other RA and animal studies (10,36,44,45), indicates that these genes could be important for the development of arthritis. One recent study demonstrated the linkage between the Lymphotoxin/LIGHT axis and IFN responses in RA patients and suggested that Lymphotoxin/LIGHT could act as an upstream modulator of IFN-signaling genes in RA (46). Furthermore, similar to our observations in DA.1HR56D rats, we found that the group of patients with mild RA showed lower expression of LST1 and higher expression of NCR3 than the group of patients with severe RA, indicating that LST1 and NCR3 could be associated with the severity of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genetic deletion of LIGHT protects mice from lung and skin inflammation and tissue remodelling in models of SSc 144,149 . Despite these results, targeting the LTαβ–LIGHT axis with baminercept, a soluble LTβR-Fc fusion protein, did not demonstrate clinical efficacy in RA and Sjögren’s syndrome (TABLE 1), although some modulation of immune reactivity was noted 150 . A caveat of these trials was the recruitment of difficult-to-treat patient populations that had previously shown inadequate responses to TNF inhibitors or other DMARDs.…”
Section: Increasing Tissue Inflammationmentioning
confidence: 99%